Strategi Digital Transformation Pemerintah Daerah: Studi Komparatif Adopsi Teknologi Smart City di Indonesia - Fadli Mappisabbi; Abd Haris; Wahyudin Zuhri (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital transformation of government has become a priority agenda in smart city development in Indonesia. This study analyzes the digital transformation strategies implemented by various local governments in adopting smart city technology through a comparative study approach. Using a qualitative methodology with multi-case analysis, this study examines five cities in Indonesia that have implemented smart city initiatives: Jakarta, Surabaya, Bandung, Yogyakarta, and Makassar. Data were collected through in-depth interviews with key stakeholders, field observations, and policy document analysis. The findings show that the success of smart city implementation is influenced by transformational leadership factors, digital infrastructure readiness, multi-stakeholder collaboration, and human resource capacity. Implementation failures are mainly caused by budget constraints, resistance to organizational change, and lack of system integration. This study provides theoretical contributions in the development of a digital transformation framework for government and practical contributions in the preparation of a smart city roadmap in Indonesia.